2,500m Isobath from Satellite Bathymetry: Accuracy Assessment in Light of IHO S-44 Standards - Marks, Karen M.; Smith, Walter H.F. (The International Hydrographic Review, 2005)
We assess the vertical (depth) and horizontal accuracy of the 2,500m isobath from satellite-derived bathymetry. We find the satellite isobath meets IHO S-44 vertical accuracy standards 90% of the time in areas of smooth topography with good acoustic survey control, but only 31% of the time in a rugged, poorly surveyed area. A horizontal displacement of the satellite isobath with respect to the NGDC Coastal Relief Model offshore of New Jersey, USA, is due to the underlying depths being uncorrected for the velocity of sound in seawater in the Model and corrected in the satellite-derived bathymetry data.